PlaSA Colombia — an Alliance-supported decision-making tool allowing students and the public and private sectors to gain a deeper insight into Colombia’s food systems. - Rankin, Sara (2024)
University students and professors — especially from private universities in Cali, Bogota, and Medellin — researchers, development agencies, non-governmental organizations and public officials are using the PlaSA Colombia tool to collect data, conduct studies, and analyses to gain deeper insights into the dynamics of the country's food system.